A key to males of Atherigona s. str. (Diptera: Muscidae) from Mali, with new records and a new species for the country - Muller, Burgert S.; Mostovski, Mike B. (Zootaxa, 2018)
Sixteen species have been found in Malaise traps and fogging samples from Kéniéroba and Ouronina, SW Mali. One new species, Atherigona kenierobaensis sp. nov., is described; A. budongoana, A. laevigata, A. lineata torrida, A. mirabilis aratra, and A. nigrapicalis are newly recorded for Mali; this brings the total number of species known from the country to 30. An illustrated identification key for Malian Atherigona species is provided.